ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA MELANJUTKAN PENDIDIKAN DI STMIK BANI SALEH - Mami Maryati; Marliza Ganefi Gumay (JURNAL LENTERA BISNIS, 2021)
Along with the increasing public awareness of higher education, it becomes a motivation to continue their education to higher education. Prospective students are faced with many choices of universities. Through promotions, it offers various study programs and displays its potential and advantages such as complete facilities and strategic locations. This study is to determine the factors that influence the decision of students to continue their education to higher education at STMIK Bani Saleh. The type of data used is primary data, namely STMIK Bani Saleh students majoring in informatics engineering with a total of 185 respondents. Data analysis used path analysis while data processing used SPSS 2.0. The results showed that the factors that influenced student decisions were cost of 26.2%, facilities of 7.1%, promotion of 2.7% and motivation of 17.56%.Key words: Factors, Decisions, Costs, Facilities, Promotion, Motivation, Student Decisions, Path Analysis